СТРАТЕГІЯ ПОЛІКУЛЬТУРНОЇ ОСВІТИ В КОНТЕКСТІ ТУРБОЛЕНТНОСТІ ПРОЦЕСІВ МІЖКУЛЬТУРНОЇ ВЗАЄМОДІЇ - Sauch, P. (Continuing Professional Education: Theory and Practice, 2019)
In the article, by analyzing the formula “unity and diversity of world cultures” and the revealed imbalance of its poles, the reasons for the practical failure of the multiculturalism project, including its educational strategies, are disclosed. Unlike multiculturalism policy, the algorithm of democraticegalitarian policy that involves not only preservation of cultural diversity, but also expanding the person’s democratic participation in the process of cultural interaction that causes the formation of new cultural groups and their incorporation into civil society is suggested. The principal novelty of this algorithm is an anthropological key to understanding of identity and harmony strategies of the formula “unity and diversity of world cultures” components balance, which provides the formation of a special, dialogical way of thinking. On this basis, the proposed new model of multicultural education as a social innovation, which is associated not only with the question “who are we?” or “where do we come from?”, but with the answer to the question “who and what we can become.”